2006
DOI: 10.1111/j.1748-5827.2006.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of 13 cases of canine respiratory disease using inhaled corticosteroids

Abstract: Inhaled corticosteroids were used for the management of chronic bronchitis and eosinophilic bronchopneumopathy in 13 dogs, and these may have the advantage of reducing side effects associated with oral corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
20

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 35 publications
0
42
0
20
Order By: Relevance
“…We hypothesized that a commonly used inhalant GC formulation (ie, fluticasone) used at a clinically relevant dose would have less systemic impact on healthy dogs than PO‐administered GC (ie, prednisone) used at an anti‐inflammatory dosage. We chose what is commonly described as an anti‐inflammatory dosage of prednisone for this study (1 mg/kg/d); this dosage has been suggested specifically for the treatment of chronic bronchitis in dogs 1,2,13 . Although the dosage chosen was typical of an initial dosing scheme, prednisone generally is tapered to the lowest effective dose (often administered on an every other day basis).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that a commonly used inhalant GC formulation (ie, fluticasone) used at a clinically relevant dose would have less systemic impact on healthy dogs than PO‐administered GC (ie, prednisone) used at an anti‐inflammatory dosage. We chose what is commonly described as an anti‐inflammatory dosage of prednisone for this study (1 mg/kg/d); this dosage has been suggested specifically for the treatment of chronic bronchitis in dogs 1,2,13 . Although the dosage chosen was typical of an initial dosing scheme, prednisone generally is tapered to the lowest effective dose (often administered on an every other day basis).…”
Section: Discussionmentioning
confidence: 99%
“…In group 3a disorders, recommended treatment is primarily symptomatic and includes cough suppression, sedation, oxygen supplementation, and, when present, control of secondary infection and inflammation. Specific examples may include, but are not limited to, glucocorticoids, opioids or other sedatives, antimicrobials, and antitussives . For management of severe tracheal collapse, placement of an intraluminal stent can be considered …”
Section: Treatmentmentioning
confidence: 99%
“…Whole lung lavage has been described to treat pulmonary alveolar proteinosis . Corticosteroids are the primary treatment for eosinophilic lung disease In dogs with group 3b2 disorders in which infection underlies pathology, appropriate antimicrobials are recommended.…”
Section: Treatmentmentioning
confidence: 99%
“…The insertion of a 16α-hydroxy group decreases mineralocorticoid activity and leads to the synthesis of triamcinolone (which also has a 9α-fluoro group). In particular the use of budesonide as an oral drug for the treatment of inflammatory bowel disease and budesonide and fluticasone propionate as inhaled medications for chronic inflammatory airway disease has recently gained popularity in dogs and cats (Bexfield et al, 2006;Padrid, 2006;Dye et al, 2013;Galler et al, 2013;Pietra et al, 2013). The effects of glucocorticoids are dose dependent, and they are classified according to their potency in relation to the potency of cortisol (Table 14-1).…”
Section: Chemistry Of Glucocorticoids and Structure-activity Relationmentioning
confidence: 99%